BARONGAN BLORA DALAM RITUS LAMPORAN: KELANGSUNGAN DAN PERUBAHANNYA The Barongan of Blora in Lamporan: their Continuity and Changes - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT This study Barongan of Blora aimed at both tracing and revealing the continuity and change of "Barongan Blora" which once was a ritual art entertainment, but which, in the course of later time, underwent transformation into a secular art. Although there has been changing from a sacred into secular art, the form of this art still has a sacred power which is a remainder of belief in animal mythology. Barongan is a sacred tiger mask dance. The wearer of mask takes on a supernatural or sacrd power totem mystic. This tiger mask may express folk beliefs mysticism, of other worlds or character of totem mystic. The presence of barongan in Lamporan is a remainder of primitive culture that still survives in an agrarian society. This still can be seen at Kunduran village. This ceremony is held once a year on Kliwon Friday or Legi Friday of Suro month at the Javanese calendar system and lasts for seven days. The development of Blora society from an agrarian society into an industrial society has resulted in a change of the Barongan in both of the continuity and change of the Barongan that happened in Blora society in this 20th, especially m the 1960s by creating Barongan as a stage art. The changing factor is caused from the situation of the Blora society that are more accupied with their accupation as farmers, merchant, civil servants, and the heterogeneous factors. Besides the factors of science and technology mastery as a result of the spread education has shown a great influence on the development of Barongan. The heritage of barongan art is so much influenced by the people's belief of barongan that has a magical protection power. The method of learning in barongan art is emphasized on nyantrik system. To gain the konwledge of Barongan and haw to produce the Barongan art, the government through its relevan field, has upgraded it by organizing a repeater course for Barongan or including the Barongan in either both of the regional or national art festival. Key word